El uso inadecuado del tiempo libre y su incidencia en los resultados de aprendizaje, de los estudiantes del sexto año de educación general básica de la Escuela Cristobal Colòn, de la ciudad de Salcedo, en el año lectivo 2014-2015 - Acurio Salguero, Carlos Fabián (2015)
The aims of this research were determine the use of free time and its impact on learning outcomes. The problem that motivated the study was: What is the impact of the inappropriate use of free time in learning outcomes, in sixth degree students of the Basic Education School Cristobal Colon, in the period 2014-2015? The methodology used was the following methods: Analytical in the analysis and interpretation of results and Synthetic in formulating conclusions, we used research techniques and instruments related to the survey and interviews that helped to gather information. The findings of this study determined that a big percentage of students use five or more hours for free time; they use the Internet, phone and TV, they don’t have an adult support, they make their tasks alone and this situation increases the disregard for the study and this generate an impact on learning outcomes. For this reason we saw the need to design a tutorial to improve the use of free time, which encourages students to practice activities on behalf of themself and they can apply it in everyday life.